Active Music Engagement and Cortisol as an Acute Stress Biomarker in Young Hematopoietic Stem Cell Transplant Patients and Caregivers: Results of a Single Case Design Pilot Study - Holochwost, Steven J.; Robb, Sheri L.; Henley, Amanda K.; Stegenga, Kristin; Perkins, Susan M.; Russ, Kristen A.; Jacob, Seethal A.; Delgado, David; Haase, Joan E.; Krater, Caitlin M. (Frontiers in Psychology, 2020)
This paper reports the results of a single case design pilot study of a music therapy intervention [the Active Music Engagement (AME)] for young children (age 3.51 to 4.53 years) undergoing hematopoietic stem cell transplantation (HCST) and their caregivers. The primary aims of the study were to determine feasibility/acceptability of the AME intervention protocol and data collection in the context of HCST. Secondary aims were to examine caregivers’ perceptions of the benefit of AME and whether there were changes in child and caregiver cortisol levels relative to the AME intervention. Results indicated that the AME could be implemented in this context and that data could be collected, though the collection of salivary cortisol may constitute an additional burden for families. Nevertheless, data that were collected suggest that families derive benefit from the AME, which underscores the need for devising innovative methods to understand the neurophysiological impacts of the AME.